Therapeutic Strategies Based on Polymeric Microparticles. (16th May 2012) - Vilos, C.; Velasquez, L. A.
Abstract : The development of the field of materials science, the ability to perform multidisciplinary scientific work, and the need for novel administration technologies that maximize therapeutic effects and minimize adverse reactions to readily available drugs have led to the development of delivery systems based on microencapsulation, which has taken one step closer to the target of personalized medicine. Drug delivery systems based on polymeric microparticles are generating a strong impact on preclinical and clinical drug development and have reached a broad development in different fields supporting a critical role in the near future of medical practice. This paper presents the foundations of polymeric microparticles based on their formulation, mechanisms of drug release and some of their innovative therapeutic strategies to board multiple diseases.